1991
DOI: 10.1002/j.2161-0045.1991.tb00318.x
|View full text |Cite
|
Sign up to set email alerts
|

Project CHOICE: Validity of Interest and Ability Measures for Student Choice of Vocational Program

Abstract: This project sought to determine whether interest and ability measures can help high school students identify vocational education programs in which they may experience satisfaction and success. Interest measures (6) and ability measures (15) were administered to 2,101 seniors in 19 area vocational‐technical schools. About 80% of the satisfied/successful seniors would have been referred, by a computer‐based score interpretation, to the job cluster containing the vocational program they completed. Generally, sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…This implies that both subject interest and academic achievement contribute to intentions. Prediger and Brandt (1991) found that a greater percentage of students chose vocational education programs based on both vocational interest and achievement scores than based on vocational interest alone.…”
mentioning
confidence: 98%
“…This implies that both subject interest and academic achievement contribute to intentions. Prediger and Brandt (1991) found that a greater percentage of students chose vocational education programs based on both vocational interest and achievement scores than based on vocational interest alone.…”
mentioning
confidence: 98%
“…IWRA's six scores are then translated to three-letter codes and World-of-Work Map regions via the procedure described in Guideline 4. Validity evidence supporting IWRA's use in career counseling has been provided by Prediger (1990), Prediger and Brandt (1991), Prediger and Swaney (1992), and Swaney (1987). Job Values (Occupational Attribute Preferences).…”
Section: Linking Uniact Scores To Occupational Optionsmentioning
confidence: 97%
“…As a result of this process, most people should end up in congruent environments-that is, environments that reward their special competencies, allow or reward expression of their values, and provide the opportunities that they seek. People do tend to have interests congruent with their educational or occupational destinations, as evidence clearly shows (Lau & Abrahams, 1972;Prediger & Brandt, 1990;Vansickle & Prediger, 1990). Other evidence implies that a congruence process also occurs in other contexts, such as mate selection (Botwin, Buss, & Shackleford, 1997;Wiggins & Weslander, 1982).…”
Section: Implications Of Holland's Theory For Satisfaction and Well-beingmentioning
confidence: 99%